Evaluasi gigi supernumerary yang menyerupai odontoma menggunakan cone beam computed tomography (CBCT) - Nova Rosdiana; Belly Sam; Lusi Epsilawati (Ikatan Radiologi Kedokteran Gigi Indonesia, 2019)
Objectives: This report is aimed to present a case about the resembling appearance of supernumerary teeth and odontoma in CBCT radiograph. Case Report: A female patient came to the radiology installation for CBCT examination of the maxillary anterior region. The patient brought a referral from the IKGA section with a diagnosis of tooth impaction 11 accompanied by odontoma. From the results of the CBCT examination, it was clear that radiopaque clearly demarcated with an irregular shape that had an enamel, dentinal structure with incomplete root formation. Conclusion: Odontoma has very similar appearance with supernumerary teeth in CBCT radiograph, understanding the specific characteristics is a need to help in diagnosis.